Academic Engagement and Academic Burnout among Medical Students: Role of Social Support, Academic Self-efficacy, and Self-Esteem: Keterlibatan Akademik dan Kelelahan Akademik pada Mahasiswa Kedokteran: Peran Dukungan Sosial, Efikasi Diri Akademik, dan Harga Diri - Yudhistira, Santi; Tiatri, Sri; Mularsih, Heni (Universitas Islam Indonesia, 2023)
Active academic engagement in the educational process is instrumental in fostering the potential and self-skills of students, as well as serving as a pathway to acquiring a quality education from academic institutions. Therefore, this study aims to examine role of factorsinfluencing academic engagement with mediators of academic burnout using path analysis through a quantitative design on 249 medical students. In this model test, academic burnout becomes a mediator variable for self-efficacy and social support, while self-esteem is tested directly on academic engagement. The measuring instruments used are UWES-SS, MSPSS, MSLQ, RSE, and MBI-SS which are tested for validity using CFA and Cronbach Alpha reliability. The results showed that academic self-efficacy and social support significantly influence engagement, mediated by burnout, while self-esteem has a direct effect on the variable. These provide further support for existing theories and prior studies, highlighting the significant impact of social support, academic self-efficacy, and self-esteem on academic engagement.